The Effect of Credit Interest Rates and Inflation on Credit Distribution in the Banking Sector Listed on the Indonesia Stock Exchange (BEI) - Kaban, Adelia Thessalonika; Alfina Hariyanti Butar-Butar; Dianty Putri Purba (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
The focus of this study is to assess the influence of loan interest rates and inflation on the spread of credit in the banking sector as a whole. The method adopted in this study is quantitative with a type of quantitative descriptive research that is explanatory in nature. The population includes all companies operating in the banking sector and listed on the Indonesia Stock Exchange as many as 46 companies, while the sample used in this study amounted to 22 companies with a purposive sampling method. The data analysis approach used is multiple linear regression. The conclusions of the analysis revealed that the significance level of 0.00 (smaller than 0.05) in the joint test confirmed that inflation and lending rates significantly affected the volume of credit disbursements in banking institutions listed on the Indonesia Stock Exchange. From the perspective of the t-test, the credit interest rate (X1) has been proven to produce a strong and statistically significant negative effect on the dependent variable (Y), in contrast to inflation (X2) which actually creates a significant positive impact on the dependent variable (Y). The results of the determination coefficient analysis showed that the adjusted Rsquare value reached 0.996. This implies that 99.6% of the fluctuations in the dependent variable Y can be explained by the independent variables X1 (Credit Interest Rate) and X2 (Inflation). Meanwhile, the other 0.4% was due to external elements that were not included in this study model.